Analisis Teori Strain dan Kontrol dalam Perspektif Kriminologi terhadap Penyimpangan Perilaku Penyebaran Konten Pornografi (International Forum of Researchers and Lecturers, 2025)
The rapid expansion of digital technology has intensified the circulation of pornographic content, making it increasingly accessible across various online platforms and posing significant risks to social, psychological, and moral stability. This study aims to examine the underlying factors contributing to the spread of pornographic content, its impact on individuals and society, and the urgency of strengthening regulatory and preventive measures. Using a qualitative approach supported by interviews and questionnaires distributed to university students in Jatinangor and Bandung, the research explores public perceptions, access patterns, and social responses regarding pornography in digital spaces. The findings reveal that most respondents consider pornography dissemination a deviant behavior, with economic motives and revenge-driven actions emerging as predominant driving factors. The study also shows that existing legal regulations are perceived as insufficient in mitigating the rapid growth of pornographic content online. These results highlight the importance of enhancing digital literacy, strengthening law enforcement, and promoting moral education to reduce the risks associated with pornography exposure. The study contributes to a deeper criminological understanding of deviant behavior in digital environments and underscores the need for collaborative societal efforts to address this phenomenon.